Desain Lower Arm Model Double Wishbone Mobil Listrik PHB Menggunakan Finite Element Metode - Budi, Sigit Setijo; Hendrawan, Andre Budhi; Usman, Muhammad Khumaidi (CV. IRA PUBLISHING, 2024)
The weight of a car's parts can be reduced by using materials such as aluminum. The lower arm is the main component of the suspension system, usually found at the front of the suspension in both Macpherson and Double Wishbone systems. There are AA6061 and malleable cast iron materials, where AA6061 is made from aluminum alloy, and the malleable cast iron material is made from steel alloy. Both are different in terms of material but almost similar in terms of material properties. The research method uses FEM assisted by Solidworks software and looks at the loading, stress and strain. The results of the research were that the material from AA6061 was better but more expensive if made in smaller quantities.